Islam & the issue of corruption - Mohamad Ezam Mohd. Nor 1967-; Waluyo, Sapto
Written by two activists from two neighbouring countrues, the book covers a whole gamut of concerns and issues central to corruption. Apart from examining the causes and consequences of corruption, it explores in depth and detail the Quranic rejection of corruption and the examples from the life of the Prophet Muhamat (may peace be upon him) that underscoe his abhorrence for the scourge.